2019
DOI: 10.1007/s10570-019-02306-2
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition of silver birch (Betula pendula Roth.) wood in Poland depending on forest stand location and forest habitat type

Abstract: We report on the most extensive study to date in Poland concerning the variability in the chemical composition of silver birch (Betula pendula Roth.) wood depending on the forest habitat type and the location of the forest stand. The research was carried out in 12 forest districts, on two habitat types where silver birch forest stands predominate in respect of coverage area and merchantable volume. Chemical composition analysis was performed on 51 samples from 306 test trees aged approximately 30, 50 and 70 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The chemical composition of the used material is similar to information found in the literature [ 23 ]. Initial characterization of the birch wood chips indicates that this it is a promising feedstock suitable for further valorization due to the high amount of glucose and xylose.…”
Section: Resultssupporting
confidence: 60%
“…The chemical composition of the used material is similar to information found in the literature [ 23 ]. Initial characterization of the birch wood chips indicates that this it is a promising feedstock suitable for further valorization due to the high amount of glucose and xylose.…”
Section: Resultssupporting
confidence: 60%
“…In view of the growing economic importance of birch wood in Poland, studies on its physical, mechanical, structural, and fuel properties were carried out, which showed that most of the studied parameters are significantly affected by location, habitat, age, and tree thickness (Lachowicz 2010a(Lachowicz , b, 2011a(Lachowicz , b, 2015Lachowicz and Paschalis-Jakubowicz 2011;Lachowicz et al 2018aLachowicz et al , b, 2019a. The influence of tree stand location and the forest habitat type on the chemical composition of birch wood was also previously studied by Lachowicz et al (2019b). The results of this research showed a statistically significant influence of stand location on all investigated components of the chemical structure of birch wood.…”
Section: Introductionmentioning
confidence: 61%
“…This increase was attributed to the water hydrophilicity of BB as a filler which bonded almost all water from the adhesive mixture, thus leading to increased formaldehyde emission over The reduction in free formaldehyde emissions may be attributed to the high amount of lignin in the chemical composition of tree bark [98,99]. BB is reported to have approximately 50% lignin content [100,101]. Lignin is capable of reacting with formaldehyde in the acidic medium, the formed benzylic alcohols react with a lignin model compound which leads to formation of methylene-linked dimers [102].…”
Section: Formaldehyde Emission From Plywood Panelsmentioning
confidence: 99%